Diagnostic value of ultrasonograpy and 99mTc-MIBI scintigraphy for preoperative localization of parathyroid adenomas - Sahin, Abdulkadir; Sakat, Muhammed Sedat; Sengoz, Furkan; Kilic, Korhan; Bilen, Arzu; Aktan, Bulent; Bilen, Habib (Annals of Medical Research, 2021)
Aim: The primary treatment of primary hyperparathyroidism (PHPT) is parathyroidectomy. With its shorter operative time and healing period, lesser general anesthesia duration, lesser hypoparathyroidism risk and better cosmetic results minimally invasive parathyroidectomy is the most commonly performed contemporary surgical procedure. However, in order for this procedure to be successful, it is important to know the location of the parathyroid adenoma. The purpose of this study was to determine the  diagnostic value of Ultrasonography (USG) and technetium methoxyisobutylisonitrile scintigraphy ( 99m Tc-MIBI) in the preoperative localization of parathyroid adenoma.Materials and Methods: Fifty-two patients diagnosed with parathyroid adenoma were included in the study. Preoperative parathyroidUSG and 99m Tc-MIBI were performed on all patients. All patients’ preoperative serum calcium, phosphorus, parathormone and Vitamin D levels, parathyroid USG and 99m Tc-MIBI, intraoperative parathyroid lesion location and histopathological examination results were recorded.Results: Patients aged between 22 and 81 (51.7±15.6) were eventually enrolled. When USG was used alone, the site of the adenoma was correctly determined in 26 of the 52 patients with a sensitivity of 52% and a positive predictive value of 92.8%. When scintigraphy was performed alone, the site of the adenoma was correctly identified in 39 of the 52 patients. Sensitivity was thus 76.4% and positive predictive value 97.5%. When USG and scintigraphy were assessed together, adenoma location was correctly identified in 45 of the 52 patients. Sensitivity for the two tests employed together was 88.2% and positive predictive value was 97.8%.Conclusions: Due to the high sensitivity of combined use of USG and 99m Tc-MIBI, we recommend the two tests to be assessed together before parathyroid surgery.
Keywords: Primary hyperparathyroidism; technetium methoxyisobutylisonitrile scintigraphy; ultrasonography